2018
DOI: 10.1590/0037-8682-0227-2017
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relation and antimicrobial resistance pattern of extended-spectrum β-lactamase- and AmpC β-lactamase-producing Enterobacter spp. isolated from different clinical samples in Tehran, Iran

Abstract: Introduction: Here, we determined the genes encoding antibiotic resistance enzymes and virulence factors and evaluated the genetic relationship between Enterobacter spp. isolated from different clinical samples. Methods: A total of 57 clinical isolates of Enterobacter spp. were tested for the production of extended-spectrum β-lactamases (ESBLs), carbapenemase, and AmpC using phenotypic and genotypic methods. Results: The most common ESBLs and AmpC β-lactamases were bla TEM (63.3%) and bla EBC (57.7%), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This finding differs with the studies of Nepalwhich reported meropenem resistance 8.8% and imipenem resistance was 10.5%. 9,13 Higher percentage of resistance in this study may be due to higher rate of use of meropenem in our hospitals. In this study, majority of urinary Enterobacter spp.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This finding differs with the studies of Nepalwhich reported meropenem resistance 8.8% and imipenem resistance was 10.5%. 9,13 Higher percentage of resistance in this study may be due to higher rate of use of meropenem in our hospitals. In this study, majority of urinary Enterobacter spp.…”
Section: Discussionmentioning
confidence: 63%
“…A study in Iran reported 77.1% isolated Enterobacter as E.cloacae and 22.8% isolates as E.aerogenes. 9 Another study in China reported 68.2% blood isolates were E.cloacae and 26.4% blood isolates were E.aerogenes. 10 Most of the Enterobacter isolates (68%) were obtained from urine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our K. aerogenes CRKA317 harbored two copies of bla AmpC gene. Several Gram-negative organisms, including E. aerogenes , Enterobacter cloacae , Serratia marcescens , Providencia stuartii , Pseudomonas aeruginosa , Hafnia alvei , and Morganella morganii , have presented AmpC in their genomes ( Jacoby, 2009 ; Ghanavati et al, 2018 ; Tamma et al, 2019 ). This enzyme provides resistance against aminopenicillins, cephalosporins, oxyimino-cephalosporins (e.g., ceftriaxone, cefotaxime, and ceftazidime), cephamycins (e.g., cefoxitin and cefotetan), and monobactams (aztreonam) ( Jacoby, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extended-spectrum cephalosporin resistant (ESC R ) Enterobacteriaceae pose a serious infection control challenge for public health [45]. The appearance of the ESC R phenotype is mainly promoted through plasmid-mediated lateral extended-spectrum β-lactamases (ESBLs) and AmpC gene transfer within Enterobacteriaceae [46].…”
Section: Discussionmentioning
confidence: 99%